A Cross-Reactive Monoclonal Antibody Against Neuraminidases of Both H9N2 and H3N2 Influenza Viruses Shows Protection in Mice Challenging Models - Wang, Fei; Wan, Zhimin; Wu, Jinsen; Wang, Yajuan; Fu, Hui; Shao, Hongxia; Qian, Kun; Gao, Wei; Ye, Jianqiang; Qin, Aijian (Frontiers in Microbiology, 2021)
Neuraminidases (NAs) of H9N2 avian influenza virus (AIV) and H3N2 human seasonal influenza virus (HSIV) share similar antigenic structures. However, there are few reports on epitopes shared by these two NAs. We previously reported a monoclonal antibody (mAb) 1G8 against the NA of H9N2 AIV with neuraminidase inhibition (NI) ability. In this study, 1G8 was shown to cross-react with and inhibit the NA of H3N2 HSIV. In a passive transfer experiment, 1G8 provided protection to mice challenged with rescued H1N2 viruses carrying H9N2 NA or H3N2 NA. Mutation at amino acid position 199 was also selected and proved to be crucial for H3N2 HSIV to escape from mAb 1G8. Moreover, we found that residue 199 contributed to inducing broad protective antibodies without the influence of the N-linked glycosylation at amino acid position 200 in NAs. Residues as residue 199, which are not shielded by glycosylation modification, would form ideal epitopes for developing universal vaccine and protective antibodies.